2007
DOI: 10.1021/es070998z
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities of Ozone and Fine Particulate Matter Formation to Emissions under the Impact of Potential Future Climate Change

Abstract: Impact of climate change alone and in combination with currently planned emission control strategies are investigated to quantify effectiveness in decreasing regional ozone and PM2.5 over the continental U.S. using MM5, SMOKE, and CMAQ with DDM-3D. Sensitivities of ozone and PM2.5 formation to precursor emissions are found to change only slightly in response to climate change. In many cases, mass per ton sensitivities to NO(x) and SO2 controls are predicted to be greater in the future due to both the lower emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
(46 reference statements)
2
34
0
Order By: Relevance
“…2050 provides an opportunity to assess the combined effects of planned emission controls and climate change. Changes in sensitivities of MDA8h O3 and 24-h average PM2.5 to emissions are primarily due to planned emission changes between 2001 and 2050 as previous results suggest that the effects of emission controls are more significant than those of climate change alone (2,6).…”
Section: Introductionmentioning
confidence: 69%
“…2050 provides an opportunity to assess the combined effects of planned emission controls and climate change. Changes in sensitivities of MDA8h O3 and 24-h average PM2.5 to emissions are primarily due to planned emission changes between 2001 and 2050 as previous results suggest that the effects of emission controls are more significant than those of climate change alone (2,6).…”
Section: Introductionmentioning
confidence: 69%
“…Liao et al (2007) examined this issue for the U.S. with the model of Tagaris et al (2007) and found no significant effect, implying that emission control strategies designed for the present climate should still be successful in the future climate. Model simulations by Baertsch-Ritter et al (2004) for the Milan urban plume show increased ozone sensitivity to NMVOCs as temperature increases, due to the reduced thermal stability of PAN and hence higher concentrations of NO x .…”
Section: Implications For Air Quality Managementmentioning
confidence: 99%
“…These relations are documented in several studies (Mickley et al, 2004;Stevenson et al, 2006;Liao et al;2007;Weaver et al, 2009). These changes may pose health risks to the population, so it is a challenge the ability of cities to adapt to and mitigate the climate change.…”
Section: Introductionmentioning
confidence: 65%